Peningkatan Kemampuan Guru SD dalam Pengolahan Data dengan Pemanfaatan Microsoft Excel - Dahriani Hakim; Ummi, Khairul; Azmi, Kaipin (LPPM Universitas Potensi Utama, 2022)
The era that is growing rapidly cannot be separated from what is called Information Technology. Information Technology is very important for us, especially for the Company when it now has to master the information technology. In addition, it also helps to manipulate data so that it looks more in accordance with the wishes and needs. Technological advances that continue to develop to date are in line with the needs of institutions in carrying out efficiency which have begun to implement all activities carried out using a computerized system. Therefore, information technology is needed in processing administrative data such as the use of Microsoft excel. The use of Microsoft Excel can help improve the quality and professionalism of workers in processing data. Excel program functions to process data automatically such as calculations, formulas, use of functions, tables, graphing and data management. for various administrative activities. From the evaluation results that have been carried out during the implementation of this training activity, it provides new understanding and knowledge for the participants, namely the teachers in utilizing the Microsoft Excel application in processing student data in the form of administrative data and student scores. During the training activities, the responses of the participants were very active and enthusiastic in following the material provided, seen from their curiosity and interest during direct trials of the exercises provided and there were few participants who took a long time to respond because of their limitations regarding the use of computers, especially in using the computer Microsoft Excel application. It is hoped that this training will have a positive influence on the participants to further explore the use of the Microsoft Excel application in processing value data and processing other school data.